Streamer-Interface-Viewer Entanglement: An Analysis on the Discursive and Affective Live-streaming Chatroom Interface - Ye, Zhen (MedieKultur: Journal of media and communication research, 2021)
In China, the live-streaming industry has a distinctive model of cultural production: showroom live-streaming. It is often adopted by social media platforms to complement other social networking activities. This study reveals the ways in which social media platforms (specifically, Douyin and Momo) design their showroom livestreaming interfaces and affordances to normalise and commodify the affective interactions between female streamers and their male viewers and to establish a gendered power relationship. Using the walkthrough method during two stages of the apps (entry to live-streaming chatrooms and the everyday use of live-streaming chatrooms), this study analyses various affordances regarding their functional, sensory, and cognitive impacts on users. This research thereby demonstrates that the live-streaming interface design constructs two types of subject positions. The ideal user is constructed as a heterosexual male, who is empowered through the consumption of virtual gifts; in contrast, the interface nudges the female streamers to conduct emotional labour and deliver implicitly sexualised performances to maintain an affective relationship with viewers.